JOB SATISFACTION OF GOVERNMENT PRIMARY SCHOOL TEACHERS: A STUDY OF SANT RAVIDAS NAGAR (BHADOHI) DISTRICT - Kumar, Rajesh; Prakash, Sumin (THE PRIMARY TEACHER, 2011)
Since the dawn of independence, social and political leaders of India have been attempting to raise the standard of living of its masses. The success of such efforts along with other factors depends to a large extent on the quality of man power, which in turn is influenced by the standard of education. The very shape of India’s future depends on the quality and quantity of the products of its educational system. Quality is at the core of education. It determines what students learn, how they learn and what benefits they draw from their education. While it is difficult to define the quality of education operationally, it can be viewed as the sum total of the quality of various components of input, process and output dimensions. Some of these components are: need-based curriculum, appropriate physical facilities, use of modern approaches to teaching, scholastic performance of students, professional preparation of teachers, and linking education to life skills and world of work